STUDI PEMANFAATAN PARTIKEL KOMPOS UNTUK PEMBUATAN BATAKO RINGAN - Maricar, Shyama; Chauf, Kusnindar Abd. (MEKTEK, 2011)
One effort to reduce the weight of the building is through the use of light particles in the concrete or mortar.For that particles of compost to be one alternative to be used. Utilization of compost particles directly willreduce the effects of environmental pollution due to garbage. Technically, in some cases the strength ofconcrete is not a determining factor but rather the ductility. Therefore in this study will be reviewed andfurther analyzed the mechanical properties of lightweight concrete that uses compost particles as basicmaterials. Mechanical properties and tensile strength referred to is the compressive strength, with normalmortar as a comparison.Based on the results of the weight of the material obtained gr/cm3 mortar respectively, cement 1.25, sand1.60, 0.31 and compost particles with water content 12%. In this case the effect of adding compost is adecrease in compressive strength of 48.74%, 68.78% decrease in tensile strength and weight reduction of9.85%. In this case the application in the manufacture of bricks is still possible, if based on a minimumcompressive strength requirement. The composition of lightweight concrete blocks with a mixture of 3%addition of compost particles are 2Semen: 6.25 Sand: 4Kompos: 2.5 water, which will produce concreteblocks with a weight of 1.89 gr/cm3 and compressive strength 7.7 MPa